Qualitative investigation of electrical conductivity in three-layer graphene structures - Dang, Linh; Oanh, Kieu; Nguyen, Lanh; Giao, (Communications in Physics, 2025)
We study the electrical conductivity \(σ_1, σ_2, σ_3\) of a three-layer graphene system made of parallel-placed monolayer graphene layers. This investigation consists of three steps. The first step is calculating the effective interactions \(W_{11}, W_{22}, W_{33}\) between impurities and electrons by using the multi-component random phase approximation. The second step is defining the dependence of \(W_{11}^2, W_{22}^2, W_{33}^2\) on interlayer distance \(d\). The last step is identifying the proportional relation between \(W_{11}^2, W_{22}^2, W_{33}^2\) and \(σ_1, σ_2, σ_3\). Based on the obtained results, we deduce the rules of change of \(σ_1, σ_2, σ_3\) when \(d\) vary. The final result is, hence, the basis for calculating the dependence of conductivity in a three-layer graphene system on other parameters.